2005
DOI: 10.1143/jjap.44.5836
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cause of Inhomogeneous Acid Distribution in Chemically Amplified Resists for Post Optical Lithography

Abstract: The quantum defect method, generalised to the spin-orbit coupling scheme, has been used to calculate the oscillator strengths of the principal series for atomic caesium, taking into account the core polarisation produced by the valence electron. The good agreement obtained with respect to experimentally measured values has led us to carry out new calculations of generalised two-photon ionisation cross sections for the atomic caesium 6s ground state with linearly and circularly polarised incident radiation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
198
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 132 publications
(199 citation statements)
references
References 31 publications
1
198
0
Order By: Relevance
“…Less electrons on oxgen atom makes radical cations of polymer unstable, or large energy barrier. The results obtained here will lead to the decrease of acid yield, which coincides with the fact that the protecting group decreases the acid yield [17][18][19][20]. Figure 17 shows the energy barrier of poly(methacrylic acid) polymers of protecting group which has the tertiary carbon atom.…”
Section: Introductionsupporting
confidence: 66%
“…Less electrons on oxgen atom makes radical cations of polymer unstable, or large energy barrier. The results obtained here will lead to the decrease of acid yield, which coincides with the fact that the protecting group decreases the acid yield [17][18][19][20]. Figure 17 shows the energy barrier of poly(methacrylic acid) polymers of protecting group which has the tertiary carbon atom.…”
Section: Introductionsupporting
confidence: 66%
“…Also, the dependence of acid generation efficiency on protection ratio of hydroxyl groups in the ionization channel was investigated and it has clarified that the selection of protecting groups is important for the acid generation efficiency. 26 Especially, it has been reported that the acid yield of polyhydroxystyrene (PHS) protected by AD gradually increases with increasing protection ratio of hydroxyl groups 27 and that the radical cation of adamantane has comparable acidity to mineral acids. 28 Therefore, a radical cation of AD seems to produce a proton and a radical cation of adamantane.…”
Section: Sensitivity Of Molecular Resist Materials Resists 1 ~mentioning
confidence: 99%
“…Although the deprotonation efficiency depends on the molecular structures of the protecting groups, the deprotonation efficiency of the protected units was set to a typical value of 0.3. [36] The preneutralization of acids before postexposure baking (PEB) [37] was assumed because annealing-type resists are generally used in EUV lithography. Using the acid distribution after the preneutralization as a boundary condition, the subsequent reaction diffusion was calculated using the reaction-diffusion equations.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%